Dimensions, structure, and morphology variations of carbon-based materials for hydrogen storage: a review - Shadykulova Assyl; Suleimenova Botakoz; Zholdayakova Saule (Discover Nano)
Abstract The swift and far-reaching evolution of advanced nanostructures and nanotechnologies has accelerated the research rate and extent, which has a huge prospect for the benefit of the practical demands of solid-state hydrogen storage implementation. Carbonaceous materials are of paramount importance capable of forming versatile structures and morphology. This review aims to highlight the influence of the carbon material structure, dimension, and morphology on the hydrogen storage ability. An extensive range of synthesis routes and methods produces diverse micro/nanostructured materials with superb hydrogen-storing properties. The structures of carbon materials used for hydrogen adsorption, from 0 to 3D, and fabrication methods and techniques are discussed. Besides highlighting the striking merits of nanostructured materials for hydrogen storage, remaining challenges and new research avenues are also considered. Graphical abstract